2021
DOI: 10.1186/s43014-021-00051-3
|View full text |Cite
|
Sign up to set email alerts
|

Ale beer containing free and immobilized Lactobacillus brevis, a potential delivery system for probiotics

Abstract: Probiotics in ale beer may be attractive to health-conscious consumers. However, beer conditions may decrease probiotic viability. Powder produced from durian (Durio zibethinus) rind, a by-product that is currently unutilized, can be used for the immobilization of probiotics. MRS medium was incubated with Lactobacillus brevis and periodically sampled to obtain the growth curve. Ale beer with free L. brevis and cells immobilized in durian rind powder was produced and separately assessed during storage at 21 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The observed variability was strain-dependent, although tolerance was compromised at 6−8%, consistent with previous reports on other LAB. 18,19 For instance, the survival rate of L. plantarum LTJ12 under the 8% alcohol stress treatment was 59.01%, 19 whereas the values obtained in that alcohol range for the L. plantarum strains in our study ranged from 52.04 to 95.78%. Nevertheless, Gold et al 20 suggested that ethanol tolerance could also be substrate-dependent, as ethanol affects specific membrane-bound proteins responsible for carbohydrate transport.…”
Section: Screening Of Strains To Evaluate Ethanol and Hopcontrasting
confidence: 54%
“…The observed variability was strain-dependent, although tolerance was compromised at 6−8%, consistent with previous reports on other LAB. 18,19 For instance, the survival rate of L. plantarum LTJ12 under the 8% alcohol stress treatment was 59.01%, 19 whereas the values obtained in that alcohol range for the L. plantarum strains in our study ranged from 52.04 to 95.78%. Nevertheless, Gold et al 20 suggested that ethanol tolerance could also be substrate-dependent, as ethanol affects specific membrane-bound proteins responsible for carbohydrate transport.…”
Section: Screening Of Strains To Evaluate Ethanol and Hopcontrasting
confidence: 54%
“…The preservation of probiotics poses a substantial challenge when applied to non-dairy products [18]. In another study, Calumba et al [19] proposed the potential of beer, the globally most consumed alcoholic beverage and the third most popular drink following water and tea, as a viable probiotic drink option. Calumba conducted research on the immobilization of Lactobacillus brevis bacteria in the alcoholic beverage Beer Ale.…”
Section: Brem Bali Innovation and Industrializationmentioning
confidence: 99%
“…One study reported the use of significant quantities of corn starch for the immobilization of probiotics [27]. Calumba et al [19] conducted research with the objective of producing probiotic ale beer, and in their study, they utilized durian powder as a means to support the immobilization of probiotic bacteria in the beer. Durian, a widely popular tropical fruit in Southeast Asia [28], is typically consumed with only a third of the fruit, while its fibrous skin constitutes more than half of its total weight [29,30].…”
Section: Brem Bali Innovation and Industrializationmentioning
confidence: 99%
“…Alcohol at higher concentrations reportedly increases membrane fluidity, thereby causing inhibition of microbial cell growth and cell death. LAB are known to survive in the presence of high alcohol concentrations (Calumba et al, 2021). NCDC 252 was also found tolerant to ethanol.…”
Section: Heat Salt and Ethanol Tolerance Of Ncdc 252mentioning
confidence: 99%